2017
DOI: 10.5301/ijbm.5000279
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between clinical toxicities and ERCC1 rs3212986 and XRCC3 rs861539 polymorphisms in cervical cancer patients

Abstract: journals.sagepub.com/home/jbm ORIGINAL RESEARCH ARTICLE characteristics (age, hemoglobin level), as well as on tumor characteristics (stage, tumor size, histological type and lymph node involvement). Current standard treatment of locally advanced cervical cancer is cisplatin-based concurrent chemoradiotherapy (CRT) (3). Although there is an improvement in survival rates, an increase in the incidence of toxicity in these patients is observed (3-5). In particular, there is concern that increased acute toxicity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…In this study, a substantial elevation in the ERCC1 gene expression in the testes was noted in comparison to the control group and the group that received ART only (Figure 3), which according to Jacobsen et al [28] strongly indicates that there is a genomic alteration and instability which could be a result of the administered CCl4 [26]. The group administered with CCl4, and ART showed a decrease in the ERCC1 gene expression compared to the CCl4 group.…”
Section: Effects Of Ccl4 and Art On Testicular Histologysupporting
confidence: 60%
See 1 more Smart Citation
“…In this study, a substantial elevation in the ERCC1 gene expression in the testes was noted in comparison to the control group and the group that received ART only (Figure 3), which according to Jacobsen et al [28] strongly indicates that there is a genomic alteration and instability which could be a result of the administered CCl4 [26]. The group administered with CCl4, and ART showed a decrease in the ERCC1 gene expression compared to the CCl4 group.…”
Section: Effects Of Ccl4 and Art On Testicular Histologysupporting
confidence: 60%
“…The ERCC1 gene is a DNA excision repair protein that assists in the repair of DNA damaged by chemicals and helps in maintaining chromosome stability [24,25]. Soares et al [26] studied the relationship between ERCC1 rs3212986 polymorphism and clinical side effects of chemotherapy and radiation for cervical cancer and reported a link between this gene and the late gastrointestinal toxicity onset. In addition, previous studies have shown the correlation between the ERCC1 status and toxicity and patient-reported quality of life [27].…”
Section: Effects Of Ccl4 and Art On Testicular Histologymentioning
confidence: 99%
“…A study showed that rs11615 polymorphism could influence the overall survival of non-small cell lung cancer patients with cisplatin-based treatment [32]. Another analysis found an association between ERCC1 rs3212986 polymorphisms and gastrointestinal toxicities in cervical cancer (p ¼ 0.038) [33]. Furthermore, a meta-analysis observed a considerable correlation between ERCC1 rs11615 and the response rate of esophageal cancer patients to neoadjuvant therapy [34].…”
Section: Discussionmentioning
confidence: 99%
“…The largest study in this cohort also reported strong GI-M prediction based on the VEGFR2 H472Q Q/Q rs1870377 genotype [66], however, this was not consistent across both cohorts included in the study. The ERCC1 rs3212986 AA genotype was associated with a greater risk of late-onset GI-M in women with cervical cancer undergoing chemoradiotherapy [67]. Systematic review showed XRCC1 rs25487 was strongly predictive of OM and GI-M risk in HSCT recipients [68], however this was not upheld in a smaller cohort of HNC patients [69].…”
Section: Cell Signalling Variantsmentioning
confidence: 98%